Colloidal Gain Media: Single‐Mode Lasing from a Single 7 nm Thick Monolayer of Colloidal Quantum Wells in a Monolithic Microcavity (Laser Photonics Rev. 15(4)/2021). Issue 4 (10th April 2021) - Foroutan‐Barenji, Sina; Erdem, Onur; Delikanli, Savas; Yagci, Huseyin Bilge; Gheshlaghi, Negar; Altintas, Yemliha; Demir, Hilmi Volkan
Abstract : In article number 2000479, Hilmi Volkan Demir and co‐workers demonstrate single‐mode lasing from an ultrathin self‐assembled monolayer of colloidal quantum wells (CQWs) with a record thickness of 7 nm. The CQWs are integrated into a high‐quality‐factor microcavity with accurate spectral/spatial alignment of the cavity mode. By overcoming the long‐pending problem of limited electrical conductivity in thicker colloidal films, such ultrathin colloidal gain media may enable electrically‐driven colloidal lasers.